Peran Perlindungan Hukum Terhadap Pasar di Era Liberalisasi Perdagangan di Indonesia - Ratu Habibah; Sri Astuti; Hilman Haetami; Abu Bakar; Fitri Raya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Investing in economic development is an important aspect because investment is one of the driving forces in the process of strengthening a country's economy. Several countries have made efforts to increase investment within the framework of their economic policies, as one way to encourage the process of strengthening the economy (Jati, 2012). Over the last decade, investment has not only become an important need for a country to advance its economic development but is also the most important means of developing industry. The research method used in this journal is qualitative. This research uses a qualitative approach to understand the factors influencing traditional markets and their impact on society and the economy. In this research, the author uses descriptive analysis to explain the conditions of traditional markets and the impact of changes in consumer preferences and the shift in people's shopping places to modern shopping centers. Indonesia has decided to become a member of both regional and world trade, such as: GATT (General Agreement on Tariffs and Trade), AFTA (Asean Free Trade Area), APEC (Asia-Pacific Economic Cooperation) and WTO (Word Trade Organization). Indonesia has become a member of regional and world trade, so at the same time, Indonesia has become part of the global community and trade liberalization. Basically, liberalization creates an era of global trade that is free of borders, protection and barriers. This also increases trade competition between economic actors. The challenges of traditional markets in facing the impact of globalization and trade liberalization are characterized by the flow of investment into Indonesia from one most profitable region to another in all investment sectors. This phenomenon makes capital investment or investment a demand to meet the needs of a country, company and society, for example by investing in the modern retail industry (modern markets), such as: supermarkets, hypermarkets, minimarkets.